Assessment of Visual Acuity and Colour Blindness Among Bus Drivers in a Metro City - Dr. Xavier. C. Jayaseelan (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Abstract The importance of good visual acuity for safe driving should be emphasized during this modern era. Most of the road traffic accidents are mainly due to poor or low visual acuity, stress and psychological factors affecting the drivers in addition to poor vehicle maintenance. An attempt was made to ascertain the visual status of the bus drivers for visual Acuity by screening them in the Poonamallee Bus Stand located in NH 4 (Chennai-Bangalore highway) frequented by many local and Interstate bus drivers, because of the high concentration of passenger movement connecting the two Metro cities of South India, a highly industrialised zone in addition to the presence of many Educational Institutions and also it is a Green Corridor. Purpose The purpose of this study was to determine the prevalence of visual impairment among bus drivers frequenting the national highways. The data from this study will provide necessary information on visual functions among bus drivers, help to make appropriate policy decisions towards drivers obtaining driving licence and regulations, and the importance of periodic vision check up and corrective measures to be undertaken. Materials and Methods A cross-sectional study was done on bus drivers passing through Poonamallee bus stand located in the busy NH 4 (Chennai – Bangalore highway). Drivers were examined for visual acuity using Snellen’s Chart, Colour Vision by Ishihara’s Isochromic Plates and Field of Vision by confrontation method. Those requiring further evaluation were referred to Saveetha Medical College and Hospital which is very close by to undergo further detailed ocular examination including Refraction and Fundus Examination. Results Totally 300 drivers were examined, out of which 214(71%) were found fit for driving. The remaining 86(29%) had visual impairment due to various causes. Conclusion Prevalence of visual impairment among drivers was about 29% which is quiet a large magnitude to be accepted. Driver fault forms a significant share of the causes of road accidents in India. With driving tests in India not emphasising in visual acuity, poor eyesight could be a major culprit in road accidents questioning passenger safety. In India the Ophthalmologist’s role in certifying a person applying to get a driver’s licence is negligible. The criteria for vision requirement for safe driving is to be revised and regular monitoring and better visual examination parameters should be given more importance for issuing and renewal of driving licenses to prevent road accidents.